Racial bias in newspaper ratings of professional football players - Francesco Principe; Jan C. van Ours (Tinbergen Institute, 2021)
We study whether there is a racial bias in ratings of professional football players in Italian newspapers. We find that there is such a bias. Conditional on objective performance indicators black players receive a lower rating than non-black players. This is not a difference across the board but predominantly present at the lower end of the newspaper rating distribution. The best black players are not subject to a racial bias in ratings. We also find that clubs do not have a racial bias in the wages they pay to players. We speculate that for clubs there is sufficient competition to remove racial wage discrimination. Clubs simply want value for money. Newspaper football experts do seem to have a racial bias in their rating of players. We hypothesize that this might be unconscious discrimination related to stereotyping of black players.
Keywords: J15; J71; L82; L83; 330; racial bias; newspaper ratings; professional football